Public reaction to Supreme Court decisions - Hoekstra, Valerie J., 1968- (Cambridge University Press, 2003)
In The Supreme Court and Local Public Opinion, Valerie Hoekstra examines public reaction to Supreme Court decisions. Using data from survey research, she finds extensive media coverage, high levels of knowledge about the cases, and that people changed how they felt about the Supreme Court in response to its decisions.